Direct expenditure effects of the Rainforest World Music Festival 2009 in Santubong, Sarawak - Shuib, Ahmad; Edman, Salbiah; Yaakub, Fazlina (Universiti Malaysia Sarawak, 2013)

(untitled)
An economic impact analysis of a tourism activity could indicate the losses in benefits to the area if the activity were not to take place in the area. The potential losses are equated to the total amount of associated expenditures of visitors spending in the area. An ex post assessment is carried out to measure the impacts of visitors expenditure in a tourism activity, the 3-day Rain Forest World Music Festival 2009 (RFWMF2009) in Santubong, Sarawak. On site data on all associated expenditures spent in the area during the festival were collected from a sample of the visitors. The results show that 34%, 18% and 48 % of the visitors have participated in 1, 2 and 3 days in the festival, respectively. The average total expenditure of per participant is about RM334 per day. A simplified Money Generation Model (MGM) is used to derive the direct economic benefits of the RFWMF2009. The festival has created RM7.4 mil in total sales, 117 new jobs and RM3.3 mil in income to the region. The local authority has received RM0.69 mil in total tax revenue. The impacts are estimates of losses that would have resulted if the festival has not taken place.